From Sensing to Responding: The Role of Digital Capability and Proactive Market Orientation in Enhancing SME Marketing Performance - Novi Handayani; Neneng Yuyu Yunida Husniawati; Muhammad Angga Anggriawan (Journal of Management and Business Innovation, 2026)
This study aims to examine how market sensing capability and proactive market orientation influence SME marketing performance through customer responsiveness, and how digital capability moderates this relationship. Grounded in dynamic capability and market orientation theories, this research develops an integrative sensing-to-responding framework. A quantitative approach was employed using SEM-PLS on 337 SMEs in Tangerang, Indonesia. Data were collected through structured questionnaires and analyzed to test direct, mediating, and moderating effects. Theoretically, this study extends the integration of dynamic capability and market orientation literature by positioning customer responsiveness as a key mediating mechanism and digital capability as a boundary condition that strengthens performance outcomes. This offers a novel explanatory pathway for understanding SME marketing performance in dynamic environments. Practically, the findings highlight that SMEs should strengthen market sensing and proactive orientation capabilities while leveraging digital tools to enhance responsiveness and market performance. Policymakers are encouraged to support digital transformation initiatives that improve SME competitiveness. However, the cross-sectional design and geographic limitation reduce generalizability. Future research should adopt longitudinal approaches and explore additional contextual variables.